Associations of changes in physical activity and well-being among cancer survivors during the COVID-19 pandemic - Natalie Cuda; Allyson Tabaczynski; Denise Bastas; Alexis Whitehorn; Golnaz Ghazinour; Linda Trinh (Advanced Exercise and Health Science)
Purpose: Meeting the physical activity (PA) guidelines (i.e., ≥ 150 min/week of aerobic PA and/or 2 days/week of resistance training) is beneficial for cancer survivors’ well-being. However, the impact of changes in PA participation during the COVID-19 pandemic on well-being of cancer survivors remains unknown. Accordingly, the purpose of this study was to examine the associations between changes in PA and well-being in cancer survivors during the COVID-19 pandemic. Methods: Cancer survivors participated in a cross sectional, online survey globally. The 20-Item Short Form Survey and the modified Godin Leisure Time Exercise Questionnaire assessed well-being and PA, respectively. Separate analysis of covariance examined well-being across PA change categories: abstainers, adopters, relapsers and maintainers. Results: Cancer survivors (N = 495; Mage=48.7 ± 15.5 years) were predominantly diagnosed with breast cancer (28.8 %). PA abstainers had significantly worse physical functioning (−19.3 points, p < 0.01; −14.0 points, p < 0.01), and role functioning (−16.6 points, p = 0.02; −12.9 points, p < 0.01) outcomes compared to adopters and maintainers, respectively. Whereas adopters had significantly less pain compared to abstainers (−13.4 points, p < 0.01) and relapsers (−11.1 points, p = 0.01) as well as better health perception than abstainers (14.2 points, p < 0.01) and relapsers (13.8 points, p < 0.01). Age (≥50 years), time since diagnosis (≥5 years), and time since treatment (<5 years) moderated the relationship between abstained or relapsed PA behavior and poor well-being outcomes. Conclusion: PA declines during the COVID-19 pandemic negatively impacted well-being outcomes in cancer survivors. Declines in well-being and PA were heightened in long-term cancer survivors who were older in age and within 5 years of treatment. Future research should identify the PA barriers specific to these cancer survivors.